VERSATILITY THY NAME IS AAMIR KHAN: THEMATIC STUDY OF THREE SELECTED FILMS - Ahmad, Afaq (International Journal of Research -GRANTHAALAYAH, 2019)
Hindi cinema has acquired a universal identity in Indian society as it is one of the most popular forms of entertainment, education and information in India. As purveyor of entertainment, Bollywood has provided a platform to many actors to flourish their talents as an actor. As far as Aamir Khan is concerned, acting is the life, blood, and soul of Aamir Khan. The way he portrays various characters in his movies, make him a perfect actor of versatile genre. Less studies have been conducted on Aamir Khan and his movies, and on the versatile portrayal of Aamir Khan contained in his movies. The purpose of this paper is to understand the versatile characteristics played by Aamir Khan in his movies. The present paper makes an attempt to critically analyse the three movies of different genres of Aamir Khan. These movies were purposively selected as Lagaan – a patriotic, productional and nostalgic movie, Rang De Basanti – a revolutionary, nationalistic and rebellious movie, and Taare Zameen Par – an inspirational, experimental and directorial movie, on account of their distinguishing stories. As the selected films etched a niche in the hearts and minds of cinemagoers and movie viewers due to their innovative stories and splendid cinematography, the thematic analysis was undertaken. It has been found from the study that message-oriented aspects depicted in these movies. Further, the informative, inspirational, patriotic, reformative, and revolutionary characteristics predominantly glimpsed in his movies. The versatile characteristics of Aamir Khan was also meticulously scrutinized. It has been found after having a critical analysis that Aamir Khan has versatile characteristics as depicted in these three selected movies under study.